Probing dopant segregation in distinct cation sites at perovskite oxide polycrystal interfaces - Hye-In Yoon (Nature Communications, 2017)
Space-charges in polycrystalline materials can drive segregation of dopants, however an in-depth understanding of this process is still missing. Here, the authors show that in polycrystalline perovskites the space-charge segregation and interfacial structure are nearly identical irrespective of the interface type.